A retrospective investigation of HLA-B*5801 in hyperuricemia patients in a Han population of China. Issue 5 (May 2018) - Cheng, Heng; Yan, Dewen; Zuo, Xin; Liu, Junying; Liu, Wenlan; Zhang, Youming
Abstract : Background: Hyperuricemia and gout have become increasingly prevalent in China. Allopurinol is an effective urate-lowering therapy, but it has severe side effects. HLA-B*5801 is highly associated with the allopurinol-induced toxic epidermal necrolysis and Stevens–Johnson syndrome. Patients and methods: In this retrospective report, we had genotyped HLA-B*5801 in 253 cases of hyperuricemia and gout patients in a Han population in Shenzhen and analyzed the clinical management of medications. Results: We found 30 carriers of the HLA-B*5801 allele in 253 cases of hyperuricemia or gout patients in the population (11.9%). Allopurinol was prescribed in both HLA-B*5801- positive and HLA-B*5801- negative groups. The evaluation of four models with or without genetic screening and management of allopurinol or febuxostat indicated that the HLA-B*5801 screening had significant cost benefit for clinical management. Conclusion: For appropriate management and cost-effectiveness, the HLA-B*5801 allele should be screened in all patients with hyperuricemia and gout in the Chinese population.